2020
DOI: 10.3389/feart.2020.00061
|View full text |Cite
|
Sign up to set email alerts
|

Observed and Projected Hydroclimate Changes in the Andes

Abstract: The Andes is the most biodiverse region across the globe. In addition, some of the largest urban areas in South America are located within this region. Therefore, ecosystems and human population are affected by hydroclimate changes reported at global, regional and local scales. This paper summarizes progress of knowledge about long-term trends observed during the last two millennia over the entire Andes, with more detail for the period since the second half of the 20th century, and presents a synthesis of clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 192 publications
(252 reference statements)
1
66
0
1
Order By: Relevance
“…projections for air surface temperature) shows agreement on the warming signal over the entire region, although temperature increases are lower than for the CMIP6 ensemble (Figure 6d). The projections toward warmer temperatures in Colombia under high GHG emission scenarios have also been reported from CMIP5 models [19][82] [83][84] [85].…”
Section: Projections Throughout the St Centurymentioning
confidence: 94%
See 2 more Smart Citations
“…projections for air surface temperature) shows agreement on the warming signal over the entire region, although temperature increases are lower than for the CMIP6 ensemble (Figure 6d). The projections toward warmer temperatures in Colombia under high GHG emission scenarios have also been reported from CMIP5 models [19][82] [83][84] [85].…”
Section: Projections Throughout the St Centurymentioning
confidence: 94%
“…Although CMIP5 and CMIP6 models improved their simulations of global climate with respect to the previous generations, they still exhibit systematic biases and uncertainties [7] [11] [12] [13] [14]. In particular, these models exhibit larger biases for precipitation than air surface temperature simulations not only at global [7] [13] but also at regional scale in northern South America, including Colombia [15] [16] [17] [18] [19] [20]. In particular, the effects of clouds and aerosols and their interactions are among the causes for these persistent biases [7] [13] [21] [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend has favored dry conditions, mainly during the summer and autumn seasons (December to April) in the southern Andes 3 (40–45°S). Dendrochronological reconstructions have shown that the present trend of the SAM is unprecedented in the last six centuries 11 , which has been evident in the precipitation and temperature of the southern Andes 12 , 13 . The trend towards a drier and warmer climate has also increased the climatic synergy with El Niño-Southern Oscillation (ENSO), promoting conditions of severe and extensive droughts 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Climate projections in the Southern Andes suggest a prolongation of the dry conditions that have affected them over the past decades 12 . General Circulation Models (GCMs) from the Coupled Model Intercomparison Project (CMIP) phase 5 indicate a latitudinal pattern of decreasing precipitation that intensifies towards the central Andes, while temperature increases mostly on the eastern slopes of the Andes 12 . The new generation of CMIP6 models has improved in many aspects.…”
Section: Introductionmentioning
confidence: 99%